(3CSGSjGJ GdQjGVjGJ GdHMJI hGdeGdjIs - (3GHQGgje Ydi GHQGgje(B, (3YHO QHgs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2004)
(3CSGSjGJ GdQjGVjGJ GdHMJI(B- (3QjGVjGJ GdJehjd hGdESJKeGQ(B- (3GdeJhGdjGJ hGdeJSdSdGJ(B- (3GdJHGOd hGdJhGab hfXQjI PGJ GdMOjf(B- (3GdeMOOGJ(B- (3GdeUahaGJ(B- (3GdOhGd hGdfgGjGJ(B- (3GdJaGVd(B- (3GdJcGeds
Keywords: (3GdQjGVjGJs; (3GdQjGVjGJ GdHMJIs; (3GdQjGVjGJ GdeGdjIs